Conversion Surgery for Patients with Advanced Gastric Cancer with Peritoneal Carcinomatosis - Ting-Ying Lee (Hindawi Limited, 2021)
Background. Patients with advanced gastric cancer (AGC) with peritoneal carcinomatosis (PC) usually have poor outcomes and high mortality risk, even with cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). This study analyzed the prognostic factors of AGC with PC and evaluated laparoscopic HIPEC (LHIPEC) plus neoadjuvant intraperitoneal and systemic chemotherapy (NIPS) as a conversion surgery for AGC patients with PC with a poor initial prognosis. Patient and Methods. We retrospectively evaluated 127 patients with AGC and PC from January 1, 2012, to March 1, 2020. After the exclusion of 32 ineligible patients, the conversion group comprised 34 patients who underwent LHIPEC + NIPS as a conversion surgery followed by CRS plus HIPEC. The CRS + HIPEC group included 15 patients who underwent CRS with HIPEC alone. Additionally, the C/T group comprised 23 patients who received systemic chemotherapy, and the palliative group comprised 23 patients who received only conservative therapy or palliative gastrectomy. Results. The conversion group demonstrated a significantly better mean overall survival compared to the CRS + HIPEC, C/T, and palliative groups (p<0.001). Patients in the conversion group who underwent LHIPEC + NIPS had significantly decreased peritoneal cancer index (PCI) scores (p<0.001) and ascites (p=0.003). Malignant ascites amount also significantly decreased after treatment in the LHIPEC + NIPS group (p<0.001). Conclusions. LHIPEC + NIPS can significantly improve the overall survival, the PCI score, and malignant ascites amount in peritoneal cytology-positive gastric cancer with PC, and an initially high PCI score. Therefore, it may be a feasible conversion strategy for AGC patients with PC.